EVALUATION OF THE CHARACTERISTICS OF THE DISTILLED GREEN ANISE ALCOHOL (Pimpinella anisum L.) OBTAINED BY SIMPLE DISTILLATION - Tunqui Quispe, Clesez (2018)
The article reports the assessment of qualitative, physical and chemical properties of the alcohol distillate of anise (Pimpinella anisum L.) obtained by simple distillation. By physicalchemical analysis an alcoholic grade of 60 to 61.9 º G.L was obtained, density from 0.907 to 0.911 g/mL, refractive index of 1.3622, freezing point lower than -10ºC, boiling point of 85 at 87 °C, acidity of 5,138 mg/100 mL and 27.05 % ester content. In the spectroscopic tests it was determined that the distillate has 1,371 mg/L of trans-anethole and 4,397 mg/L of p-anisaldehyde. According to thin layer chromatography analysis, where toluene:ethyl acetate (93: 7) was used as a mobile phase and silica gel 60 F254 chromate plates as a stationary phase, an Rf of 0.86 and 0.48 was reported for the mobile phases, which indicates the high presence of trans-anethole; the p-anisaldehyde was not detected. In the HPLC tests the presence of trans-anethole in 0.1104 % and the absence of p-anisaldehyde were checked. Finally, the presence of four (04) components was detected through the GC-MS tests: trans-anethole as the major compound (92.7 %), 1,4-methanocycloocta [d] pyridazine (3.2 %), estragole (2.08 %) and phthalic acid, di- (1-hexen-5-yl) ester (2.02 %). These data will allow, in the future, to analyze the anise distillate properties to improve the quality of the alcoholic beverages which are produced base on it in the liquor industry where this work was carried out.